Effect of Sustained Use of Aspirin until the Time of Surgery on Outcomes following Coronary Artery Bypass Grafting: A Randomized Clinical Trial - Sharifi, Mehrzad; Kamali, Alireza; Ghandi, Yazdan (The Thoracic and Cardiovascular Surgeon, 2018)
Background The topic of aspirin (acetylsalicylic acid, ASA) use in coronary artery disease patients planned for coronary artery bypass grafting during perioperative period is among the most disputed issues in cardiac surgery. We designed a study to weigh the risks and benefits of continued ASA ingestion until the time of surgery.Methods In this randomized double-blind clinical trial, 206 consecutive patients scheduled for isolated coronary artery bypass surgery (CABG) were randomly stratified into two groups. In group 1 (104 cases), patients were given 80 mg ASA per day until the day of surgery. In group 2 (102 patients), ASA (80 mg per day) was stopped 4 days before the operation. Patients in these two groups were similar in terms of preoperative patient and procedural characteristics. ASA was resumed 24 hours after the surgery in all patients.Results The rates of bleeding and reexploration within 24 hours of surgery were significantly higher in group 1 (824.3 vs. 492.1 mL, p < 0.001 and 5.7% vs. 0, p = 0.0138, respectively). The amount of intra- and postoperative packed red blood cell (PRBC) transfusion was considerably greater in group 1 (mean: 1.83 vs. 0.71 units, p < 0.001). The rate of hospital mortality was similar (1.9% in both the groups, p = 0.98). Patients in group 1 had significantly longer mean hospital stay than patients in group 2 (8 vs. 5.1 days, p < 0.001). Again the time interval between weaning from heart–lung machine and closing the sternum was strikingly longer in group 1 (mean: 32.1 vs. 14.5 minutes, p < 0.001). The incidence of adverse postoperative outcomes such as myocardial infarction, stroke, and renal failure was not statistically different between the two groups.Conclusion Sustained ASA use until the day of surgery in patients planned for elective isolated CABG can result in excessive bleeding, increased rate of reexploration, and need for more PRBC transfusion without any proven beneficial effect on reducing unfavorable postoperative outcomes. Hence, we recommend discontinuing ASA between 3 and 5 days before non-urgent CABG while keeping it on in nonelective circumstances.
Keywords: aspirin; coronary artery bypass grafting; postoperative hemorrhage